CONCEPTUAL PROBLEMS AND RECENT PROGRESS IN FLUVIAL SEQUENCE STRATIGRAPHY - Rhee Ch.W. (My University, 2006)
Although sequence stratigraphic analysis on marine successions have revolutionized interpretation of sedimentary records since the 80's, those on inland fluvial successions have been hampered due to complex responses of a fluvial system to allogenic and autogenic controls. Such a complexity combined with the vague definition of accommodation in an inland fluvial setting, makes it difficult to divide the fluvial successions into genetic packages based on key surfaces such as sequence boundary, marine flooding or regressive surfaces. It means that the application of sequence stratigraphic concept to fluvial successions requires quite different approach to the definition and recognition of fluvial sequence. Current fluvial sequence stratigraphy models emphasizing the role of base-level in accommodation change are not the cases. They oversimplify the relationship between accommodation and alluvial architecture, without considering the difference in organization and nature of stratigraphic records between the marine and the inland fluvial system. The models do not provide a standard procedure for the analysis of fluvial successions without detailed studies on the key surfaces and thus do not predict the nature of stratigraphic records of an inland fluvial system. In this article, recent reports and different perspectives on the spatial and temporal variation of fluvial successions are reviewed in order to shed light on the efforts toward the establishment of new fluvial sequence stratigraphy model which should be conceptually sound and methodologically objective, enabling the fluvial successions to be interpreted in the more flexible and predictable way even in subsurface data.
Keywords: FLUVIAL SEQUENCE STRATIGRAPHY; FLUVIAL SYSTEM; ALLUVIAL ARCHITCCTURE; PALCOSOLS; STREAM POWER